2021
DOI: 10.1109/access.2021.3105188
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Positioning System Using Synthetic Training and Data Fusion

Abstract: Indoor Positioning Systems (IPSs) are used to estimate the position of mobile devices in indoor environments. Fingerprinting is the most used technique because of its higher accuracy. However, this technique requires a labor-intensive training phase that measures the Received Signal Strength Indicator (RSSI) at all Reference Points (RPs) locations. On the other hand, model-based IPSs use signal propagation models to estimate distances from RSSI. Thus, they do not require expensive training but result in higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A novel intelligent positioning system (IPS) is suggested that enhances the precision of mobile device location by merging signal propagation models and particle swarm optimization (PSO). 44 The signal propagation model is utilized to simulate the attenuation and reflection of wireless signals in each particle, and the PSO method is used to optimize the position estimation process by creating distinct particles in the map. The optimal parameters of the signal propagation model do not need to be known, nor does the suggested MIPS-PSO system require any prior training.…”
Section: Enhances Localization Precisionmentioning
confidence: 99%
“…A novel intelligent positioning system (IPS) is suggested that enhances the precision of mobile device location by merging signal propagation models and particle swarm optimization (PSO). 44 The signal propagation model is utilized to simulate the attenuation and reflection of wireless signals in each particle, and the PSO method is used to optimize the position estimation process by creating distinct particles in the map. The optimal parameters of the signal propagation model do not need to be known, nor does the suggested MIPS-PSO system require any prior training.…”
Section: Enhances Localization Precisionmentioning
confidence: 99%
“…First, it has advantages in the straightforward implementation, the second there are disadvantages point that becomes a focal point, especially for the database enhancement in our proposal. RSSI is defined as the received power, and it follows the log-loss distance model [36]:…”
Section: Figure 1 Distance Measurement Techniquementioning
confidence: 99%